"The keyboard lits the écran": the cinematographic poetry of Manuel Gusmão - Lima, Marleide Anchieta de (2012)
The poetry of Manuel Gusmão invests intensively in interart relations. His works offervisual dialogue with painting, photography and, above all, experience the dynamics of the cinema. For this reason, our study aims to examine the construction imagery in poems of the author mentioned, but not limited to thematic scope, since it will investigate the implementation of cinematic techniques for composition and textual meanings that express such procedures in an attempt to say or maybe not to say, the object being viewed. With this pesrpective, we turn to the theoretical-critical of George Didi-Huberman, Jacques Aumont, Gilles Deleuze, and the prose of Herberto Helder in Photomaton & Vox.